SIGNS AND APPEARANCE OF ECONOMIC HELPLESSNESS (Conference Zone, 2022)
The article scientifically analyzes questions about the signs of financial insolvency of enterprises in the conditions of market relations, about their manifestation and achievement of financial stability..